Preparation method and application of high-strength wear-resistant heat-conducting composition and silica gel sheet

By using thermal fillers and coupling agents in the back clip of the mobile phone, the thermal conductivity and mechanical properties of silicone are enhanced, and the problems of difficult to take into account in the prior art are solved, and the preparation of high-strength wear-resistant thermal conductivity silicone skin is realized, providing an efficient and durable heat dissipation solution.

CN119613967APending Publication Date: 2025-03-14DONGGUAN YIBEI NUCLEAR TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411660298.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high thermal conductivity and wear resistance in the mobile phone back clip, resulting in unstable material performance and complex production process.

Method used

High-strength wear-resistant thermally conductive compositions are prepared by adding a thermally conductive filler such as alumina or boron nitride to the silicone matrix and using the first coupling agent to enhance the binding force of the filler and the silicone, combining the ball milling treatment and appropriate raw material ratio.

Benefits of technology

The thermal conductivity is higher than 1.25W/mK, the tensile strength and tear strength are significantly improved, and can withstand more than 150,000 folds, and the wear amount in friction is less than 0.1mg, providing an efficient and durable heat dissipation solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143144350000151
    Figure BDA0005143144350000151
Patent Text Reader

Abstract

The invention relates to the technical field of silica gel sheets, in particular to a high-strength wear-resistant heat-conducting composition and a preparation method and application of a silica gel sheet. The invention discloses a high-strength wear-resistant heat-conducting composition which comprises the following components in parts by weight: 1-5 parts of methyl vinyl silicone rubber; 15 to 20 parts of vinyl silicone oil; 2-10 parts of white carbon black; 0.5-1 part of a first coupling agent; 50-70 parts of a heat conducting filler; 0.1 to 0.2 part of a chain extender; 5-10 parts of a cross-linking agent; 0.01 to 0.02 part of a catalyst; and 0.01 to 0.05 part of a polymerization inhibitor. According to the silica gel sheet provided by the invention, the binding force between the filler and the silica gel matrix is enhanced through the high heat conduction characteristic of the heat conduction filler powder and the treatment of the coupling agent, so that the overall heat conduction performance of the material is improved. Meanwhile, by controlling the particle size and the shape of the filler and adopting methods such as ball milling treatment, the mechanical property of the material is ensured, and the stable performance can be kept in long-time use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone rubber, and in particular to a high-strength wear-resistant heat-conductive composition and a preparation method and application of silicone rubber. Background Art

[0002] As smartphones become increasingly intelligent, especially with the rapid development of artificial intelligence (AI) technology and mobile games, the workload of the chips inside the phone has increased significantly, causing the phone to generate a lot of heat during operation. Traditional mobile phone designs mainly rely on the phone's own cooling system to manage this heat, but with the improvement of chip performance and the limitation of the internal space of the phone, it is difficult to effectively deal with the high temperature problem by relying solely on the cooling mechanism inside the phone. In order to improve this situation, external cooling devices such as mobile phone back clips have appeared on the market, which can effectively transfer the heat generated by the phone, thereby achieving a cooling effect.

[0003] In the design of a mobile phone back clip, the material selection between the phone back shell and the back clip is crucial. The ideal material should not only have good thermal conductivity to ensure that heat can be quickly transferred from the phone to the back clip, but also have excellent friction resistance to ensure that it will not be damaged by frequent contact during daily use. However, existing technical solutions have encountered challenges in achieving these two requirements.

[0004] Although the pure silicone rubber on the market has good strength and wear resistance, its thermal conductivity is low and cannot meet the needs of efficient heat conduction. On the other hand, the method of improving the thermal conductivity by adding a large amount of thermal conductive powder to the silicone matrix can enhance the thermal conductivity of the material to a certain extent, but it greatly weakens the mechanical properties of the material. This type of thermal conductive silicone will be damaged after slight folding or surface friction, which is far from reaching the at least 100,000 friction lifespan required by the back clip.

[0005] Moreover, due to the uneven addition and distribution of thermal conductive powder, the performance of the final product will fluctuate greatly and the consistency between different batches will be poor, which not only affects the product quality, but also increases production costs and control difficulty.

[0006] In summary, although there are some solutions for mobile phone back clip heat dissipation materials on the market, these solutions generally have problems such as difficulty in balancing thermal conductivity and wear resistance, unstable material properties, and complex production processes. Therefore, developing a new type of thermal conductive silicone skin with both high thermal conductivity and excellent wear resistance has become a technical problem that needs to be solved urgently. Summary of the invention

[0007] The present application provides a preparation method and application of a high-strength wear-resistant thermal conductive composition and a silicone rubber skin, which enhances the bonding force between the filler and the silicone matrix through the high thermal conductivity of the thermal conductive filler powder (such as aluminum oxide, boron nitride, etc.) and the treatment of the first coupling agent, thereby improving the overall thermal conductivity of the material. At the same time, by controlling the particle size and shape of the filler and using methods such as ball milling, the mechanical properties of the material are ensured, so that it can maintain stable performance even in long-term use.

[0008] The technical solution adopted by this application to solve its technical problem is:

[0009] In a first aspect, the present application provides a high-strength wear-resistant thermally conductive composition, comprising the following components in parts by weight:

[0010] 1 to 5 parts of methyl vinyl silicone rubber;

[0011] 15-20 parts of vinyl silicone oil;

[0012] 2-10 parts of white carbon black;

[0013] 0.5 to 1 part of the first coupling agent;

[0014] 50-70 parts of thermal conductive filler;

[0015] Chain extender 0.1-0.2 parts;

[0016] 5-10 parts of cross-linking agent;

[0017] Catalyst 0.01-0.02 parts;

[0018] 0.01 to 0.05 parts of polymerization inhibitor;

[0019] The thermal conductive filler is any one or more of aluminum oxide, boron nitride, zinc oxide, aluminum hydroxide, silicon powder, and barium sulfate.

[0020] In one or more technical solutions, the methyl vinyl silicone rubber is a vinyl-terminated methyl vinyl silicone rubber with a vinyl content of 0.16-0.18%.

[0021] In one or more technical solutions, the vinyl silicone oil is a vinyl silicone oil with a viscosity of 50 to 500 cps.

[0022] In one or more technical solutions, the particle size of the white carbon black is 50 to 200 nm.

[0023] In one or more technical solutions, the first coupling agent is any one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0024] In one or more technical solutions, the chain extender is a side-group hydrogen-containing silicone oil; and the cross-linking agent is a terminal-group hydrogen-containing silicone oil.

[0025] In one or more technical solutions, the catalyst is a platinum catalyst.

[0026] In one or more technical solutions, the polymerization inhibitor is acetylene cyclohexanol.

[0027] In a second aspect, the present application provides a method for preparing a silicone rubber containing a high-strength wear-resistant thermally conductive composition according to the first aspect, comprising the following steps:

[0028] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0029] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender are added to a kneader, kneaded at 150 to 200 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0030] S3. Add the kneaded product obtained in step S2 together with the thermal conductive filler, cross-linking agent, catalyst and polymerization inhibitor into an open mill, mix well and evacuate; then roll into a sheet, and solidify in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0031] In a third aspect, the present application provides an application of a high-strength, wear-resistant, and thermally conductive composition, wherein the silicone rubber described in the first aspect or the silicone rubber prepared by the preparation method described in the second aspect is applied to electronic devices as a heat dissipation material.

[0032] The beneficial effects of this application are:

[0033] The high-strength, wear-resistant, and thermally conductive silicone composition described in the present application comprises a first coupling agent that can enhance the interfacial bonding force between the silicone and the thermally conductive powder, thereby improving the overall performance of the composite material; thermally conductive filler powders, such as alumina, boron nitride, etc., rapidly conduct the heat generated inside the equipment to the outside through their high thermal conductivity; chain extenders and cross-linking agents are used to adjust the cross-linking density of the silicone, thereby improving the elasticity and wear resistance of the silicone while ensuring strength; catalysts and inhibitors are used to control the vulcanization process of the silicone to ensure that the product has stable performance.

[0034] The high-strength wear-resistant thermally conductive silicone rubber described in this application has excellent wear resistance and tear strength while maintaining high thermal conductivity. The thermal conductivity of the thermally conductive silicone rubber of this application is greater than 1.25W / mK, and the highest is 1.44W / mK, which is much higher than traditional silicone materials and can effectively conduct the heat generated by the mobile phone. The tensile strength is above 8.7MPa, and the highest is 11.2MPa; the tear strength is above 26.1KN / m, and the highest is 32.5KN / m, which shows that it can remain stable during long-term use and is not easy to break. The number of folding times exceeds 150,000 times, and the wear amount is less than 0.1mg (1000 turns). This feature is particularly important for mobile phone radiators that need to be frequently plugged in and out.

[0035] Therefore, the thermally conductive silicone rubber of the present application provides an efficient, durable and reliable solution for smartphone heat dissipation, and is expected to be widely used in the field of smartphone heat dissipation. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0037] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0038] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.

[0039] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0040] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0041] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0042] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0043] The present application provides a high-strength wear-resistant thermally conductive composition, comprising the following components in parts by weight:

[0044] 1 to 5 parts of methyl vinyl silicone rubber;

[0045] 15-20 parts of vinyl silicone oil;

[0046] 2-10 parts of white carbon black;

[0047] 0.5 to 1 part of the first coupling agent;

[0048] 50-70 parts of thermal conductive filler;

[0049] Chain extender 0.1-0.2 parts;

[0050] 5-10 parts of cross-linking agent;

[0051] Catalyst 0.01-0.02 parts;

[0052] 0.01 to 0.05 parts of polymerization inhibitor;

[0053] The thermal conductive filler is any one or more of aluminum oxide, boron nitride, zinc oxide, aluminum hydroxide, silicon powder, and barium sulfate.

[0054] Specifically, the thermal conductive filler can improve the thermal conductivity of the material. In the present application, the thermal conductive filler is selected in an amount of 50 to 70 parts, for example, 50 parts, 55 parts, 60 parts, or 70 parts. If the amount of the thermal conductive filler is too small, the thermal conductivity of the material is insufficient; if the amount of the thermal conductive filler is too large, the mechanical properties of the material will be significantly reduced.

[0055] The thermal conductive filler may be alumina, which is spherical in shape, with a particle size of 0.1 to 10 μm, and a center particle size of 0.1 μm, 0.4 μm, 1 μm, 2 μm, 3 μm, 5 μm, or a combination of several thereof;

[0056] Boron nitride is hexagonal boron nitride, flaky or spherical in shape, with a particle size of 0.1 to 10 μm;

[0057] Zinc oxide is in the form of four-needle whiskers with a particle size of 0.1 to 10 μm;

[0058] Aluminum hydroxide is spherical in shape and has a particle size of 0.1 to 10 μm;

[0059] Silica powder is spherical silicon dioxide with a particle size of 0.1 to 1 μm;

[0060] Barium sulfate is spherical barium sulfate with a particle size of 0.1 to 10 μm;

[0061] In one or more embodiments, the methyl vinyl silicone rubber is a vinyl terminated methyl vinyl silicone rubber with a vinyl content of 0.16-0.18%.

[0062] Specifically, methyl vinyl silicone rubber is used as a base material to provide basic physical properties of silicone rubber, such as mechanical strength, temperature resistance and elasticity. Vinyl-terminated methyl vinyl silicone rubber with a vinyl content of 0.16-0.18% has good mechanical properties and temperature resistance and can remain stable at high temperatures.

[0063] In the present application, methyl vinyl silicone rubber is selected in 1 to 5 parts, for example, it can be 1 part, 2 parts, 3 parts, and 5 parts. If the amount of methyl vinyl silicone rubber is too little, it will lead to insufficient substrate and affect the overall performance of the material; if the amount of methyl vinyl silicone rubber is too much, it will increase the hardness of the material and reduce its flexibility.

[0064] In one or more embodiments, the vinyl silicone oil is a vinyl silicone oil with a viscosity of 50 to 500 cps.

[0065] Specifically, vinyl silicone oil acts as a plasticizer to improve the fluidity of silicone rubber and enhance the processing performance of the material. Vinyl silicone oil with a viscosity of 50 to 500 cps can reduce the viscosity of silicone rubber, making it easier to process, while improving the softness and elasticity of the material.

[0066] The weight proportion of vinyl silicone oil is 15 to 20 parts, specifically 15 parts, 16 parts, 17 parts, 19 parts, 20 parts. If the amount of vinyl silicone oil is too little, the fluidity of the material is poor and processing is difficult; if the amount of vinyl silicone oil is too much, the mechanical properties of the material will decrease.

[0067] In one or more embodiments, the particle size of the white carbon black is 50 to 200 nm.

[0068] Specifically, white carbon black is used as a reinforcing agent to improve the mechanical strength and wear resistance of silicone rubber. White carbon black with a particle size of 50 to 200 nm is a nano-scale filler that can significantly enhance the tensile strength and tear strength of silicone rubber.

[0069] The weight proportion of white carbon black is 2 to 10 parts, specifically 2 parts, 5 parts, 6 parts, 7 parts, 9 parts, 10 parts. If the amount of white carbon black is too little, the mechanical properties of the material will be insufficient; if the amount of white carbon black is too much, the hardness of the material will increase and its flexibility will be reduced.

[0070] In one or more embodiments, the first coupling agent is any one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0071] Specifically, the first coupling agent improves the interface bonding between the filler and the substrate, and improves the compatibility and uniformity of the material. Silane coupling agents, titanate coupling agents, and aluminate coupling agents can promote chemical bonding between the filler and the substrate, and improve the overall performance of the material.

[0072] The weight proportion of the first coupling agent is 0.5 to 1 part, specifically 0.5 part, 0.6 part, 0.7 part, or 1 part. If the first coupling agent is used in too little amount, the bonding force between the filler and the substrate will be insufficient, thus affecting the performance of the material. If the first coupling agent is used in too much amount, the cost of the material will increase, and other side effects may be caused.

[0073] More specifically, the silane coupling agent is one or a combination of A151 (vinyl triethoxysilane), A171 (vinyl trimethoxysilane), A172 (vinyl tri(β-methoxyethoxy) silane);

[0074] The titanate coupling agent is: a monoalkoxy titanate coupling agent, specifically triisostearyl isopropyl titanate;

[0075] The aluminate coupling agent is: distearoyloxyisopropyl aluminate.

[0076] In one or more embodiments, the chain extender is a side-group hydrogen-containing silicone oil with a hydrogen content of 0.01 to 0.05%; the cross-linking agent is a terminal-group hydrogen-containing silicone oil with a hydrogen content of 0.16 to 0.20%.

[0077] Specifically, the chain extender can extend the molecular chain of silicone rubber, improve the fluidity and processing performance of the material, and the side-group hydrogen-containing silicone oil can increase the molecular chain length of silicone rubber, improve its fluidity and processing performance.

[0078] The weight proportion of the chain extender is 0.1 to 0.2 parts, specifically 0.1 parts, 0.13 parts, 0.16 parts, 0.18 parts, and 0.2 parts. If the amount of the chain extender is too small, the fluidity of the material is insufficient and processing is difficult; if the amount of the chain extender is too large, the mechanical properties of the material will be reduced.

[0079] Crosslinking agents promote the crosslinking reaction of silicone rubber and improve the mechanical properties and heat resistance of the material. End-group hydrogen-containing silicone oil can form a crosslinking structure between silicone rubber molecular chains, improving the strength and temperature resistance of the material.

[0080] The weight proportion of the crosslinking agent is 5 to 10 parts, specifically 5 parts, 6 parts, 7 parts, 8 parts, and 10 parts. If the amount of the crosslinking agent is too small, the crosslinking degree is insufficient, and the mechanical properties and heat resistance of the material are poor; if the amount of the crosslinking agent is too large, the hardness of the material will increase and its flexibility will decrease.

[0081] In one or more embodiments, the catalyst is a platinum catalyst with a pt content of 500 to 5000 ppm.

[0082] Specifically, the catalyst accelerates the cross-linking reaction of silicone rubber and shortens the curing time. Platinum catalyst can effectively promote the cross-linking reaction and improve production efficiency.

[0083] The weight proportion of the catalyst is 0.01 to 0.02 parts, specifically 0.01 parts, 0.013 parts, 0.016 parts, 0.018 parts, and 0.02 parts. If the catalyst is used in too little amount, the cross-linking reaction rate is slow and the curing time is long; if the catalyst is used in too much amount, the cost of the material will increase, and it may cause excessive cross-linking and affect the material properties.

[0084] In one or more embodiments, the inhibitor is acetylene cyclohexanol.

[0085] Specifically, the polymerization inhibitor prevents premature cross-linking of silicone rubber during processing, ensuring the processing performance of the material. Acetylene cyclohexanol can inhibit the occurrence of cross-linking reactions, ensuring that the material maintains good fluidity during processing.

[0086] The weight proportion of the polymerization inhibitor is 0.01 to 0.05 parts, specifically 0.01 parts, 0.02 parts, 0.03 parts, and 0.05 parts. If the dosage of the polymerization inhibitor is too small, the material may undergo premature crosslinking during processing, affecting the processing performance; if the dosage of the polymerization inhibitor is too large, the final crosslinking degree of the material will be reduced, affecting the performance.

[0087] Therefore, in the high-strength wear-resistant thermal conductive silicone rubber, the various raw materials interact with each other to jointly improve the comprehensive performance of the material. The following is a detailed description of the synergistic effect between the various raw materials and their technical principles:

[0088] 1. Methyl vinyl silicone rubber and vinyl silicone oil

[0089] Synergistic effect: Methyl vinyl silicone rubber as a base material provides the basic physical properties of the material, such as mechanical strength, elasticity and temperature resistance. Vinyl silicone oil as a plasticizer improves the fluidity of silicone rubber and improves the processing performance of the material.

[0090] Methyl vinyl silicone rubber has a high molecular weight and cross-linking density, which can provide good mechanical properties. The addition of vinyl silicone oil reduces the viscosity of silicone rubber, making it easier to process, while improving the softness and elasticity of the material. The combination of the two makes the material have better processability and flexibility while maintaining good mechanical properties.

[0091] 2. White carbon black and the first coupling agent

[0092] Synergistic effect: As a reinforcing agent, white carbon black improves the mechanical strength and wear resistance of silicone rubber. The first coupling agent improves the interface bonding between white carbon black and silicone rubber substrate, enhancing the compatibility and uniformity of the materials.

[0093] Silica is a nano-scale filler with a high specific surface area, which can significantly enhance the tensile strength and tear strength of silicone rubber. The first coupling agent promotes the combination between silica and the silicone rubber substrate through chemical bonding, forming a more stable network structure, thereby improving the overall performance of the material. This synergistic effect enables the material to maintain good mechanical properties under high load and high friction conditions.

[0094] 3. Thermally conductive filler powder and second coupling agent

[0095] Synergistic effect: Thermally conductive filler powder (such as alumina, boron nitride, etc.) improves the thermal conductivity of the material. The second coupling agent improves the interface bonding between the thermally conductive filler and the silicone rubber substrate, and improves the dispersibility and compatibility of the thermally conductive filler.

[0096] Thermally conductive filler powder has a high thermal conductivity coefficient and can effectively transfer heat. The second coupling agent forms a chemical bond between the thermally conductive filler and the silicone rubber substrate through surface modification, which improves the dispersibility and compatibility of the thermally conductive filler, thereby enhancing the thermal conductivity of the material. This synergistic effect allows the material to have good mechanical properties and processing properties while maintaining high thermal conductivity.

[0097] 4. Chain extenders and cross-linkers

[0098] Synergistic effect: Chain extenders extend the molecular chain of silicone rubber, improving the fluidity and processing performance of the material. Cross-linking agents promote the cross-linking reaction of silicone rubber, improving the mechanical properties and heat resistance of the material.

[0099] Chain extenders improve the fluidity and processing properties of silicone rubber by extending its molecular chains, making it easier to form. Crosslinkers form crosslinked structures between silicone rubber molecular chains through crosslinking reactions, improving the strength and temperature resistance of the material. The combination of the two gives the material good fluidity and formability during processing, and excellent mechanical properties and heat resistance after curing.

[0100] 5. Catalysts and inhibitors

[0101] Synergistic effect: The catalyst accelerates the cross-linking reaction of silicone rubber and shortens the curing time. The inhibitor prevents the silicone rubber from premature cross-linking during processing and ensures the processing performance of the material.

[0102] Catalysts (such as platinum catalysts) can effectively promote the cross-linking reaction of silicone rubber, accelerate the curing speed, and improve production efficiency. Inhibitors inhibit the occurrence of cross-linking reactions, ensuring that the material maintains good fluidity during processing and prevents premature cross-linking. The combination of the two makes the material have good fluidity and processing performance during processing, and at the same time has excellent mechanical properties and heat resistance after curing.

[0103] In a second aspect, the present application provides a method for preparing the high-strength, wear-resistant, thermally conductive silicone rubber described in the first aspect, comprising the following steps:

[0104] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0105] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender are added to a kneader, kneaded at 150 to 200 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0106] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0107] Specifically, in step S3, the thermal conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermal conductive filler and the second coupling agent, dry ball milling is adopted, and corundum balls are used as the ball milling medium. The mass ratio of the thermal conductive filler to the balls is 1:1. The ball milling is carried out at 1200 rpm for 2 hours to obtain the ball-milled thermal conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermal conductive filler. Before ball milling, the thermal conductive filler is in powder form, and the second coupling agent is first used for ball milling. The surface of the treated ball-milled thermal conductive filler composite powder has rich functional groups. These functional groups also improve the compatibility during polymer fusion, which is reflected in the good tear strength and friction resistance of the silicone rubber.

[0108] More specifically, the second coupling agent is distearoyloxyisopropylaluminate.

[0109] In a third aspect, the present application provides an application of a high-strength, wear-resistant, and thermally conductive composition, wherein the silicone rubber described in the first aspect or the silicone rubber prepared by the preparation method described in the second aspect is applied to electronic devices as a heat dissipation material.

[0110] Example 1

[0111] A high-strength wear-resistant heat-conductive composition comprises the following components in parts by weight:

[0112] 1 part of methyl vinyl silicone rubber, which is vinyl terminated and has a vinyl content of 0.16%;

[0113] Vinyl silicone oil (viscosity 50cps) 15 parts;

[0114] 2 parts of white carbon black (particle size 50nm);

[0115] Coupling agent (silane coupling agent A151) 0.5 parts;

[0116] 50 parts of thermal conductive filler (spherical alumina with a particle size of 0.1 μm);

[0117] Chain extender (side-group hydrogen-containing silicone oil, hydrogen content is 0.01%) 0.1 part;

[0118] 5 parts of cross-linking agent (terminal hydrogen-containing silicone oil, hydrogen content is 0.16%);

[0119] Catalyst (platinum catalyst) 0.01 part;

[0120] Polymerization inhibitor (acetylene cyclohexanol) 0.01 parts.

[0121] The method for preparing the above-mentioned high-strength wear-resistant thermally conductive silicone rubber comprises the following steps:

[0122] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0123] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender were added to a kneader, kneaded at 150 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0124] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0125] In step S3, the thermally conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermally conductive filler and the second coupling agent, dry ball-milling is performed, using corundum balls as ball-milling media, with a mass ratio of the thermally conductive filler to the balls of 1:1, and ball-milling is performed at 1200 rpm for 2 hours to obtain the ball-milled thermally conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermally conductive filler, and the second coupling agent is distearoyloxyisopropylaluminate.

[0126] Example 2

[0127] A high-strength wear-resistant heat-conductive composition comprises the following components in parts by weight:

[0128] 5 parts of methyl vinyl silicone rubber, wherein the methyl vinyl silicone rubber is a methyl vinyl silicone rubber terminated with a vinyl content of 0.18%;

[0129] Vinyl silicone oil (viscosity 500cps) 20 parts;

[0130] 10 parts of white carbon black (particle size 200 nm);

[0131] Coupling agent (isopropyl triisostearyl titanate) 1 part;

[0132] 70 parts of thermal conductive filler (spherical boron nitride with a particle size of 10 μm);

[0133] Chain extender (side-group hydrogen-containing silicone oil, hydrogen content is 0.05%) 0.2 parts;

[0134] Cross-linking agent (terminal hydrogen-containing silicone oil, hydrogen content is 0.20%) 10 parts;

[0135] Catalyst (platinum catalyst) 0.02 parts;

[0136] Inhibitor (acetylene cyclohexanol) 0.05 parts.

[0137] The method for preparing the above-mentioned high-strength wear-resistant thermally conductive silicone rubber comprises the following steps:

[0138] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0139] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender were added to a kneader, kneaded at 200 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0140] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0141] In step S3, the thermally conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermally conductive filler and the second coupling agent, dry ball-milling is performed, using corundum balls as ball-milling media, with a mass ratio of the thermally conductive filler to the balls of 1:1, and ball-milling is performed at 1200 rpm for 2 hours to obtain the ball-milled thermally conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermally conductive filler, and the second coupling agent is distearoyloxyisopropylaluminate.

[0142] Example 3

[0143] A high-strength wear-resistant heat-conductive composition comprises the following components in parts by weight:

[0144] 3 parts of methyl vinyl silicone rubber, wherein the methyl vinyl silicone rubber is a methyl vinyl silicone rubber terminated with a vinyl content of 0.17%;

[0145] Vinyl silicone oil (viscosity 200cps) 18 parts;

[0146] 8 parts of white carbon black (particle size 100 nm);

[0147] Coupling agent (distearoyloxyisopropylaluminate) 0.8 parts;

[0148] 60 parts of thermal conductive filler (zinc oxide with a particle size of 5 μm);

[0149] Chain extender (side-group hydrogen-containing silicone oil, hydrogen content is 0.03%) 0.15 parts;

[0150] 7 parts of cross-linking agent (terminal hydrogen-containing silicone oil, hydrogen content is 0.18%);

[0151] Catalyst (platinum catalyst) 0.015 parts;

[0152] Polymerization inhibitor (acetylene cyclohexanol) 0.03 parts.

[0153] The method for preparing the above-mentioned high-strength wear-resistant thermally conductive silicone rubber comprises the following steps:

[0154] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0155] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender were added to a kneader, kneaded at 180 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0156] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0157] In step S3, the thermally conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermally conductive filler and the second coupling agent, dry ball-milling is performed, using corundum balls as ball-milling media, with a mass ratio of the thermally conductive filler to the balls of 1:1, and ball-milling is performed at 1200 rpm for 2 hours to obtain the ball-milled thermally conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermally conductive filler, and the second coupling agent is distearoyloxyisopropylaluminate.

[0158] Example 4

[0159] A high-strength wear-resistant heat-conductive composition comprises the following components in parts by weight:

[0160] 2 parts of methyl vinyl silicone rubber, which is vinyl terminated and has a vinyl content of 0.16%;

[0161] Vinyl silicone oil (viscosity 80cps) 1 6 parts;

[0162] 3 parts of white carbon black (particle size 80nm);

[0163] Coupling agent (silane coupling agent A171) 0.6 parts;

[0164] 55 parts of thermal conductive filler (spherical aluminum hydroxide with a particle size of 1 μm);

[0165] Chain extender (side-group hydrogen-containing silicone oil, hydrogen content is 0.02%) 0.12 parts;

[0166] 6 parts of cross-linking agent (terminal hydrogen-containing silicone oil, hydrogen content is 0.17%);

[0167] Catalyst (platinum catalyst) 0.012 parts;

[0168] Inhibitor (acetylene cyclohexanol) 0.02 parts.

[0169] The method for preparing the above-mentioned high-strength wear-resistant thermally conductive silicone rubber comprises the following steps:

[0170] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0171] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender were added to a kneader, kneaded at 160 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0172] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0173] In step S3, the thermally conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermally conductive filler and the second coupling agent, dry ball-milling is performed, using corundum balls as ball-milling media, with a mass ratio of the thermally conductive filler to the balls of 1:1, and ball-milling is performed at 1200 rpm for 2 hours to obtain the ball-milled thermally conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermally conductive filler, and the second coupling agent is distearoyloxyisopropylaluminate.

[0174] Example 5

[0175] A high-strength wear-resistant heat-conductive composition comprises the following components in parts by weight:

[0176] 4 parts of methyl vinyl silicone rubber, wherein the methyl vinyl silicone rubber is a methyl vinyl silicone rubber with vinyl end-capping and a vinyl content of 0.17%;

[0177] Vinyl silicone oil (viscosity 400cps) 19 parts;

[0178] 9 parts of white carbon black (particle size 150nm);

[0179] Coupling agent (isopropyl triisostearyl titanate) 0.9 parts;

[0180] Thermally conductive filler (spherical barium sulfate with a particle size of 8 μm) 68 parts;

[0181] Chain extender (side-group hydrogen-containing silicone oil, hydrogen content is 0.04%) 0.18 parts;

[0182] 9 parts of cross-linking agent (terminal hydrogen-containing silicone oil, hydrogen content is 0.18%);

[0183] Catalyst (platinum catalyst) 0.017 parts;

[0184] Polymerization inhibitor (acetylene cyclohexanol) 0.04 parts.

[0185] The method for preparing the above-mentioned high-strength wear-resistant thermally conductive silicone rubber comprises the following steps:

[0186] S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind;

[0187] S2. The ground material obtained in step S1 and the first coupling agent and the chain extender were added to a kneader, kneaded at 190 ° C for 2 hours, cooled for standby use, to obtain a kneaded material;

[0188] S3. Add the kneaded product obtained in step S2 and the ball-milled thermal conductive filler, cross-linking agent, catalyst, and polymerization inhibitor into an open mill, mix them evenly, and then evacuate them; then roll them into sheets, and solidify them in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

[0189] In step S3, the thermally conductive filler is first ball-milled before being added to the mixing mill. The ball-milling process is as follows: after mixing the thermally conductive filler and the second coupling agent, dry ball-milling is performed, using corundum balls as ball-milling media, with a mass ratio of the thermally conductive filler to the balls of 1:1, and ball-milling is performed at 1200 rpm for 2 hours to obtain the ball-milled thermally conductive filler, wherein the amount of the second coupling agent added is 0.15% of the weight of the thermally conductive filler, and the second coupling agent is distearoyloxyisopropylaluminate.

[0190] Comparative Example 1

[0191] No vinyl silicone oil was added, and the other conditions were the same as those in Example 1.

[0192] Comparative Example 2

[0193] No white carbon black was added, and the other conditions were the same as those in Example 1.

[0194] Comparative Example 3

[0195] The first coupling agent was not added, and the other conditions were the same as those in Example 1.

[0196] Comparative Example 4

[0197] No chain extender was added, and the other conditions were the same as those in Example 1.

[0198] Comparative Example 5

[0199] No crosslinking agent was added, and the other conditions were the same as those in Example 1.

[0200] Comparative Example 6

[0201] No catalyst was added, and the other conditions were the same as in Example 1.

[0202] The thermally conductive silicone rubbers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were subjected to the following performance tests, and the relevant results are summarized in Table 1:

[0203] 1. Thermal conductivity

[0204] The thermal conductivity of the material was measured using a thermal conductivity meter (LFA467 HyperFlash laser flash thermal conductivity meter) under standard conditions.

[0205] 2. Tensile strength

[0206] The tensile test was performed using a universal material testing machine (such as Instron 5985) according to ASTM D412 standard.

[0207] 3. Tear strength

[0208] The tear test was performed using a universal material testing machine (such as Instron 5985) according to ASTM D624 standard.

[0209] 4. Number of folds

[0210] Use a folding tester (such as Tinius Olsen H10KT) to perform a folding test and record the number of folds the material can withstand without breaking.

[0211] 5.Abrasion Resistance

[0212] Use an abrasion tester (such as Taber 5750) to perform abrasion tests according to ASTM D4060 and record the amount of wear on the material.

[0213] Table 1

[0214]

[0215] From Table 1, it can be seen that the thermal conductivity of the silicone rubbers of Examples 1-5 is greater than 1.25 W / mK, and the highest is 1.44 W / mK (Example 2). This shows that these silicone rubbers have high thermal conductivity and can effectively conduct heat away from the inside of the device.

[0216] The tensile strength of the silicone rubbers of Examples 1-5 is above 8.7 MPa, and the highest is 11.2 MPa (Example 2), which indicates that these silicone rubbers have good mechanical strength and can maintain structural integrity when subjected to external forces.

[0217] The tear strength of the silicone rubbers of Examples 1-5 is above 26.1 KN / m, and the highest reaches 32.5 KN / m (Example 2), which indicates that these silicone rubbers have excellent tear resistance and are not easily broken when scratched by sharp objects.

[0218] The silicone skins of Examples 1-5 can be folded more than 150,000 times, which indicates that these silicone skins have excellent flexibility and durability and are not easily damaged even when frequently bent.

[0219] The wear amount of the silicone rubber of Examples 1-5 is less than 0.1 mg (1000 revolutions), which indicates that these silicone rubbers have good wear resistance and can maintain the integrity of the surface during long-term use.

[0220] From Table 1, we can see that:

[0221] In terms of thermal conductivity, the thermal conductivity of Examples 1-5 is all above 1.25 W / mK, while the thermal conductivity of Comparative Examples 1-7 is all lower than or equal to 1.25 W / mK, especially Comparative Example 1 (without adding vinyl silicone oil) and Comparative Example 3 (without adding coupling agent), the thermal conductivities are 1.01 W / mK and 1.15 W / mK, respectively, which are significantly lower than the embodiments.

[0222] In terms of tensile strength, the tensile strengths of Examples 1-5 are all above 8.7 MPa, while the tensile strengths of Comparative Examples 1-7 are all lower than 8.7 MPa, especially Comparative Example 1 (without adding vinyl silicone oil) and Comparative Example 2 (without adding white carbon black), the tensile strengths are 7.2 MPa and 7.5 MPa respectively, which are significantly lower than the embodiments.

[0223] In terms of tear strength, the tear strengths of Examples 1-5 are all above 26.1 KN / m, while the tear strengths of Comparative Examples 1-7 are all lower than 26.1 KN / m, especially Comparative Example 1 (without adding vinyl silicone oil) and Comparative Example 2 (without adding white carbon black), the tear strengths are 20.2 KN / m and 22.4 KN / m respectively, which are significantly lower than the examples.

[0224] In terms of the number of folding times, Examples 1-5 are all more than 150,000 times, while Comparative Examples 1-7 are all less than 150,000 times, especially Comparative Example 1 (without adding vinyl silicone oil) and Comparative Example 2 (without adding white carbon black), which are folded 100,000 times and 120,000 times respectively, which are significantly lower than the embodiments.

[0225] In terms of wear resistance, the wear amounts of Examples 1-5 are all less than 0.1 mg (1000 revolutions), while the wear amounts of Comparative Examples 1-7 are all greater than 0.1 mg, especially Comparative Example 1 (without adding vinyl silicone oil) and Comparative Example 2 (without adding white carbon black), the wear amounts are 0.3 mg and 0.23 mg respectively, which are significantly higher than the embodiments.

[0226] Therefore, it can be seen that:

[0227] Comparative Example 1 does not add vinyl silicone oil, resulting in a significant decrease in thermal conductivity, tensile strength, tear strength, folding times and abrasion resistance. This shows that vinyl silicone oil plays a key role in improving the thermal conductivity, mechanical properties and processing properties of the material.

[0228] Comparative Example 2 does not add white carbon black, resulting in a significant decrease in tensile strength, tear strength and folding times. This shows that white carbon black plays an important role in improving the mechanical properties and wear resistance of the material.

[0229] In comparative example 3, the first coupling agent was not added, resulting in a decrease in thermal conductivity, tensile strength, tear strength and folding times. This shows that the first coupling agent plays an important role in improving the interface bonding between the filler and the substrate and improving the thermal conductivity and mechanical properties of the material.

[0230] Comparative Example 4 does not add a chain extender, resulting in a decrease in tensile strength, tear strength and folding times. This shows that the chain extender plays an important role in improving the fluidity and processing properties of the material, thereby enhancing the mechanical properties.

[0231] Comparative Example 5 does not add a crosslinking agent, resulting in a significant decrease in tensile strength, tear strength and folding times. This shows that the crosslinking agent plays an important role in improving the mechanical properties and heat resistance of the material.

[0232] Comparative Example 6 did not add a catalyst, resulting in a decrease in tensile strength, tear strength and folding times. This shows that the catalyst plays an important role in accelerating the cross-linking reaction and improving production efficiency and material performance.

[0233] In Comparative Example 7, the second coupling agent is not added, and the silicone rubber of Comparative Example 7 is inferior to that of Example 1 in terms of thermal conductivity, tensile strength, tear strength, number of folding times and wear resistance.

[0234] Because the second coupling agent plays a key role in interface bonding and performance enhancement in the material. Specifically: the second coupling agent improves the thermal conductivity of the material by improving the bonding between the thermal conductive filler and the silicone rubber matrix. The lack of the second coupling agent will lead to a decrease in the dispersibility and compatibility of the thermal conductive filler, thereby affecting the thermal conductivity; the second coupling agent improves the tensile strength and tear strength of the material by enhancing the bonding force between the filler and the matrix. The lack of the second coupling agent will lead to a decrease in the overall mechanical properties of the material; the second coupling agent improves the flexibility and wear resistance of the material, allowing the material to maintain good performance during long-term use. The lack of the second coupling agent will make the material more susceptible to damage and wear after multiple bending and friction.

[0235] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A high-strength wear-resistant thermally conductive composition, characterized in that: The composition comprises the following components in parts by weight: 1 to 5 parts of methyl vinyl silicone rubber; 15-20 parts of vinyl silicone oil; 2-10 parts of white carbon black; 0.5 to 1 part of the first coupling agent; 50-70 parts of thermal conductive filler; Chain extender 0.1-0.2 parts; 5-10 parts of cross-linking agent; Catalyst 0.01-0.02 parts; 0.01 to 0.05 parts of polymerization inhibitor; The thermal conductive filler is any one or more of aluminum oxide, boron nitride, zinc oxide, aluminum hydroxide, silicon powder, and barium sulfate.

2. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The methyl vinyl silicone rubber is a vinyl-terminated methyl vinyl silicone rubber with a vinyl content of 0.16-0.18%.

3. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The vinyl silicone oil is a vinyl silicone oil with a viscosity of 50 to 500 cps.

4. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The particle size of the white carbon black is 50 to 200 nm.

5. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The first coupling agent is any one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

6. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The chain extender is a side-group hydrogen-containing silicone oil; and the cross-linking agent is a terminal-group hydrogen-containing silicone oil.

7. The high-strength wear-resistant thermally conductive silicone rubber according to claim 1, characterized in that: The catalyst is a platinum catalyst.

8. The high-strength wear-resistant heat-conductive silicone rubber according to claim 1, characterized in that: The polymerization inhibitor is acetylene cyclohexanol.

9. A method for preparing a silicone rubber containing a high-strength wear-resistant thermal conductive composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The methyl vinyl silicone rubber, vinyl silicone oil and white carbon black were mixed and ground with a three-roll mill until it became a uniform semisolid fluid state to obtain a grind; S2. The ground material obtained in step S1 and the first coupling agent and the chain extender are added to a kneader, kneaded at 150 to 200 ° C for 2 hours, cooled for standby use, to obtain a kneaded material; S3. Add the kneaded product obtained in step S2 together with the thermal conductive filler, cross-linking agent, catalyst and polymerization inhibitor into an open mill, mix well and evacuate; then roll into a sheet, and solidify in a tunnel furnace to obtain a high-strength thermal conductive silicone rubber.

10. An application of a high-strength wear-resistant thermally conductive composition, characterized in that: The thermally conductive composition according to any one of claims 1 to 8 or the silicone rubber prepared by the preparation method according to claim 9 is used as a heat dissipation material in electronic equipment.

Citation Information

Cited By

  • Stain-resistant and wear-resistant silicone rubber compound and preparation method thereof

    CN120442052A

  • Anti-fouling wear-resistant silicone rubber and preparation method thereof

    CN120442052B